Pengaruh Pemberian Makanan Tambahan (PMT) Berbahan Pangan Lokal terhadap Status Gizi Balita: Studi Pra-Eksperimental di Puskesmas Minasatene Kabupaten Pangkep - Halisah, Halisah; Tambaip, Titus; Putri, Hanriska Awidiya; Tarnoto, Tenny; Ekawati, Erni Agit; Burhanuddin, Yuniarti Ekasaputri (Mando Care Jurnal, 2025)
Nutritional problems in toddlers remain a public health challenge, especially in areas with a high prevalence of stunting and malnutrition, such as Pangkep Regency. One of the interventions implemented by the government is the provision of supplementary feeding (PMT) made from local foods to improve the nutritional status of toddlers. This study aims to determine the effect of providing PMT made from local foods on the nutritional status of toddlers in the working area of ​​the Minasatene Community Health Center, Pangkep Regency. This study used a quantitative design with a pre-experimental one-group pretest–posttest approach. The study was conducted in August 2025 with a sample of 49 toddlers who received PMT, using a total sampling technique. Data were collected by measuring body weight before and after the PMT intervention for 60 days, then analyzed using a paired t-test. The results showed an increase in toddler body weight after PMT administration, with a change in nutritional status from undernutrition and severe malnutrition to mostly normal nutrition. Statistical tests showed a significant difference between body weight before and after the intervention (p<0.05). It can be concluded that the provision of PMT made from local foods has a significant effect on improving the nutritional status of toddlers in the working area of ​​the Minasatene Community Health Center, Pangkep Regency.